Pengaruh Penerapan Akuntansi Biaya dan SAK ETAP terhadap Keterandalan Laporan Keuangan pada Pabrik Minyak Kelapa Sawit PT. Anugerah Tanjung Medan (PT. ATM) dengan Komitmen Manejerial sebagai Variabel Moderasi - Dhany, Ahmad; Rafika, Mulya; Al Ihsan, Muhammad Ali (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
This study aims to analyze the effect of cost accounting implementation and Financial Accounting Standards for Entities without Public Accountability (SAK ETAP) on the reliability of financial statements, with managerial commitment as a moderating variable at the Palm Oil Mill of PT. Anugerah Tanjung Medan. This research employs a quantitative approach using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method. Data were collected through questionnaires distributed to 100 employees of the company. The results indicate that cost accounting implementation has a positive and significant effect on the reliability of financial statements and serves as the most dominant factor in improving financial reporting quality. The implementation of SAK ETAP also shows a positive and significant influence, although with a lower effect size. However, managerial commitment does not moderate the relationship between cost accounting and financial statement reliability. In contrast, managerial commitment significantly moderates the relationship between SAK ETAP and financial statement reliability, but with a negative direction, indicating a weakening effect. The R-Square value of 0.649 suggests that the model explains 64.9% of the variance in financial statement reliability. This study implies that optimizing cost accounting practices and consistently implementing accounting standards are crucial to improving financial reporting quality, while the role of managerial commitment requires further evaluation in accounting policy implementation.